Characterization of a monoclonal antibody to turnip mosaic virus and its use in immunodiagnosis of infection - Horsewood, P.; McDermott, M.R.; Stobbs, L.W.; Brais, P.L.J.; Underdown, B.J. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1991)
Monoclonal antibodies specifie for turnip mosaic virus (TuMV) were produced and used in a double antibody sandwich enzyme immunoassay to detect virus in infected plants. One particular antibody from a hybridoma clone having desirable growth, specificity and antibody production properties was characterized in detail. This antibody was shown by immunocytochemical electron microscopy and immunoblotting to react with a virion coat protein. Conditions providing efficient extraction of virus from leaves were investigated by using the antibody in both capture and detection steps of a sandwich immunoassay. With an extraction buffer System containing multiple detergents, a highly sensitive assay was produced that reliably detected virus in infected plants. This assay is now in routine use for immunodiagnosis of turnip mosaic virus infections.